2021
DOI: 10.1002/agj2.20768
|View full text |Cite
|
Sign up to set email alerts
|

White clover living mulch enhances soil health vs. annual cover crops

Abstract: Cover crops can improve soil health by increasing soil organic matter, soil porosity, permeability, and crop yield. Yet, land planted to cover crops are often limited by economic constraints. Perennial living mulch (LM) cover crops may provide better benefits to soil health because they are actively growing throughout the year and selfregenerate without reseeding. The objective of this study was to compare the impact of a white clover (Trifolium repens L.) LM vs. annual cover crops on soil health traits. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Because the weeds take up most of the space in CCCR treatments, the overall production was greater than WC. These results reveal that annual winter species, such as crimson clover and cereal rye are suited as cover crops (Andrews et al, 2020;Hill et al, 2021;Sanders et al, 2018;Xu et al, 2021) and not as an annual LM as we attempted in our study.…”
Section: Mulch Massmentioning
confidence: 57%
See 2 more Smart Citations
“…Because the weeds take up most of the space in CCCR treatments, the overall production was greater than WC. These results reveal that annual winter species, such as crimson clover and cereal rye are suited as cover crops (Andrews et al, 2020;Hill et al, 2021;Sanders et al, 2018;Xu et al, 2021) and not as an annual LM as we attempted in our study.…”
Section: Mulch Massmentioning
confidence: 57%
“…Although in optimal conditions the WC can supplement the N required for corn growth, its decreased persistence in the third year did not confer any production advantages to the WC when compared to CCCR or control. It is important to note, however, that WC LM systems can improve soil health metrics that may support longer term productivity and reduce the need for inputs of herbicides and fertilizers (Hill et al., 2021). Yet, the 2‐year study was not sufficiently long enough to test the long‐term productivity and soil health in this case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the measurements of the average maize yields in 2018, Hill et al (2021) reported that similar yields were found for CC (14.73 Mg ha −1 ) and CR (16.06 Mg ha −1 ), while statistically significantly lower yields under LM (12.78 Mg ha −1 ). Achieving both soil health and increased yields remains a challenge.…”
Section: Ghg Fluxes In 2018mentioning
confidence: 60%
“…For example, specific cover crops have been used to enhance soil biota to increase the yield of the subsequent crop (132). Living mulch has often been studied in the context of vegetable crop production, where it has been shown to provide multiple benefits (133)(134)(135). In the phytotechnology toolbox, both cover crops and intercropping/ living mulch can improve the diversity and the perenniality of agroecosystems.…”
Section: Cover Crops and Intercroppingmentioning
confidence: 99%